Ketakutan akan Kematian Orang yang Beragama Katolik Ditinjau dari Keterlibatan dalam Kelompok Kategorial - Dicky Susilo; Monika Septiani Nogo Choban (Psychopreneur Journal, 2022)
Death can come at any time, this causes a person to experience the fear of death. Fear of death is experienced not only by those who are on the verge of death (severely ill), but also by healthy people. One of the factors that can influence the fear of death is religiosity. One way to increase religiosity is by being involved in categorical groups, associations of the Christian faithful that are ecclesiastical in nature. The hypothesis of this study is that there is a difference in fear of death between people who are involved in the categorical group and those who are not. The research participants were 139 Catholics, consisting of 54 people who were involved and 85 people who were not. Sampling was based on purposive sampling technique and used the Collett-Lester Fear of Death Scale. The results of the analysis showed the results of t=3.353 (p<0.05) which means there is a significant difference in fear of death. The results of the study indicate the need for Catholics to increase their religiosity through involvement in categorical groups to reduce the fear of death.